Risk of Colorectal Cancer in Patients With Irritable Bowel Syndrome: A Meta-Analysis of Population-Based Observational Studies - Wu, Xinhui; Wang, Jingxi; Ye, Zhen; Wang, Jin; Liao, Xibei; Liv, Mengsi; Svn, Zhen (Frontiers in Medicine, 2022)
Background and Aims: Evidence on the association between irritable bowel syndrome (IBS) and colorectal cancer (CRC) risk is inconsistent. Therefore, we aimed to examine whether IBS leads to an increased risk for CRC using a systematic review and meta-analysis approach. Methods: PubMed, Embase, and Web of Science were systematically searched to identify all relevant literature published through July 30, 2021. The pooled risk ratios (RRs) and corresponding 95% confidence intervals (CIs) for CRC after diagnosis of IBS were computed using random-and fixed-effects models and stratified by age, follow-up time, gender, and study design. The quality of included studies was assessed by the Newcastle-Ottawa scale. Results: We included six studies consisting of 1,085,024 participants. Overall, the risk of detecting CRC after the initial IBS diagnosis was significantly higher than non-IBS controls (RR=1.52, 95% CI: 1.04-2.22, P=0.032). The peak of elevated risk occurred within the first year of IBS diagnosis (RR=6.84, 95% CI: 3.70-12.65, P<0.001), and after one year, the risk of CRC was similar to that of the general population (RR=1.02, 95% CI: 0.88-1.18, P=0.813). Notably, we found that the RR of CRC was more significant in IBS patients younger than 50 years compared to those older than 50 years (RR=2.03, 95% CI: 1.17-3.53, P=0.012 vs. 1.28, 95%CI: 0.94-1.75, P=0.118, respectively). Gender and study design did not affect the results. Conclusion: Current evidence does not support that IBS leads to an increased incidence of CRC, and the early excess risk is more likely attributable to misclassification resulting from overlapping symptoms rather than causation. Clinicians must remain vigilant for the CRC risk in patients younger than 50 years with IBS-like symptoms to avoid delaying necessary screening.